A new phylogeny of the cladoxylopsid plexus: contribution of an early cladoxylopsid from the Lower Devonian (Emsian) of Quebec. Issue 10 (19th October 2021) - Durieux, Thibault; Lopez, Madeleine A.; Bronson, Allison W.; Tomescu, Alexandru M. F.
Abstract: Premise: Cladoxylopsids formed Earth's earliest forests and gave rise to the ancestors of sphenopsids and ferns. Lower Devonian (Emsian) strata of the Battery Point Formation (Quebec, Canada) contain new anatomically preserved cladoxylopsids, one of which is described in this article. To assess the phylogenetic position of this fossil and address questions of cladoxylopsid phylogeny, we conducted a comprehensive phylogenetic study. Methods: Permineralized axes were studied in serial sections using the cellulose acetate peel technique. We evaluated phylogenetic relationships among cladoxylopsids using a data set of 36 new morphological characters and 31 species, in parsimony‐constrained analyses. Results: We describe Adelocladoxis praecox gen. et sp. nov., a cladoxylopsid with small actinostelic axes bearing dichotomously branched, helically arranged ultimate appendages and fusiform sporangia. Adelocladoxis provides the oldest evidence of cladoxylopsid anatomy, including ultimate appendages and sporangia. In agreement with non‐phylogenetic classification schemes, our phylogenetic analysis resolves a basal grade of iridopterids and a clade of cladoxylopsids s.s ., which includes a pseudosporochnalean cladoxylopsid clade, a cladoxylalean cladoxylopsid clade, and Adelocladoxis . Conclusions: Our phylogenetic analysis illuminates aspects of tempo and mode of evolution in the cladoxylopsid plexus. Originating prior to the Emsian, cladoxylopsids reached global distribution by the Frasnian. Iridopterids and cladoxylopsids s.s . radiated in the Emsian‐Eifelian. The sequence of character change recovered by our phylogeny supports a transition from actinostelic protosteles to dissected steles, associated with an increase in xylem rib number and medullation generating a central parenchymatous area.